Development of the agricultural science in Tuva - Chysyma, Roza B. (The New Research of Tuva, 2014)
Article presents the author’s presentation at International Science Conference devoted to 100th  jubilee "United Tuva in united Russia: history, modernity, futures” (July 3-4, 2014, Kyzyl). It handles information on a history of creation, establishments and development of the agricultural science in the Republic of Tuva.
Keywords: Tuvan agricultural experiments station; Tuvan agricultural research institute; husbandry; seedage; forage production; cattle breeding; veterinary science; rural economics